2019
DOI: 10.3928/01913913-20190808-01
|View full text |Cite
|
Sign up to set email alerts
|

Strabismus Surgery Infection Prophylaxis and Timing of First Postoperative Visit

Abstract: Purpose: To characterize the practice patterns of pediatric ophthalmologists regarding infection prophylaxis for strabismus surgery and timing of the first postoperative visit. Methods: A ten-question multiple-choice, close-ended questionnaire was e-mailed to members of the American Association for Pediatric Ophthalmology and Strabismus listserv. Survey responses were summarized using frequencies and percentages. Univariable tests of association between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…A recent multicenter study by DeBenedictis et al investigated practice patterns for infection prophylaxis in pediatric ophthalmic strabismus surgery. Specialists (members of the American Association for Pediatric Ophthalmology and Strabismus) responded to a survey (completed by 380 members) that showed 88.4% use topical administration of 5% povidone iodine during surgical preparation, 90% use topical antibiotics with or without steroids at the end of surgery, and 85.5% prescribe oral or topical antibiotics after surgery [44].…”
Section: Scenario #2 Pediatric Patient Undergoing Extraocular Surgerymentioning
confidence: 99%
“…A recent multicenter study by DeBenedictis et al investigated practice patterns for infection prophylaxis in pediatric ophthalmic strabismus surgery. Specialists (members of the American Association for Pediatric Ophthalmology and Strabismus) responded to a survey (completed by 380 members) that showed 88.4% use topical administration of 5% povidone iodine during surgical preparation, 90% use topical antibiotics with or without steroids at the end of surgery, and 85.5% prescribe oral or topical antibiotics after surgery [44].…”
Section: Scenario #2 Pediatric Patient Undergoing Extraocular Surgerymentioning
confidence: 99%
“…Based on these findings, we adapted our postoperative treatment in strabismus surgery in 2017 from routine use of topical antibiotics taken over a week to a onetime drop of polyvidone-iodine. However, in 2019, a survey among 380 members of the American Association for Pediatric Ophthalmology and Strabismus revealed that 85.5 % still prescribe oral or topical antibiotics postoperatively [4].…”
Section: Introductionmentioning
confidence: 99%